THE INFLUENCE OF USING VOICE BLOG ON STUDENTS’ SPEAKING ABILITY OF ANALYTICAL EXPOSITION (ELT Forum: Journal of English Language Teaching, 2012)
AbstractTujuan dari penelitian ini adalah untuk mengamati bagaimana blog suara digunakan untuk mengajar eksposisi analitis lisan dan untuk mengamati apakah blog suara memberikan perbedaan yang signifikan dalam meningkatkan kemampuan siswa berbicara tentang analisis eksposisi.Desain penelitian adalah eksperimental kuantitatif.Teknik pengumpulan data menggunakan Tes lisan, dan rubrik evaluasi.Data dianalisis menggunakan formula uji-t, untuk mengetahui apakah ada perbedaan yang signifikan antara skor rata-rata kelompok eksperimen dan kelompok kontrol. Hasil penelitian menunujkkan skor rata-rata post test kelompok eksperimen lebih tinggi kelompok kontrol. Oleh karena nilai t hitung lebih tinggi dari t tabel-, maka itu berarti ada perbedaan yang signifikan antara kemampuan analitis siswa yang diajarkan menggunakan blog suara dibanding mereka yang diajarkan tanpa blog suara.The objectives of the study was to observe how voice blog is used to teach spoken analytical exposition and to observe whether or not voice blog gives significant difference in improving students’ speaking ability of analytical exposition.To achieve the objectives of the study, an experimental quantitative research was conducted. Spoken test, and rubric of evaluation were used to collect the data. The technique to analyze the data was t-test formula. It was used as a technique to determine whether there was any significant difference between the means of the score of the experimental and the control group or not. The mean score of the post-test of the experimental group was higher than the mean of post-test of the control group. And the t obtained value (4.703) was higher than the t critical table (1.67). Since the t-test was higher than the t-table, then it means that there was a significant difference of the spoken analytical exposition text score of the students who were taught using voice blog to the score of those who were taught without voice blog.